Rituximab for the Treatment of Relapses in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis1. Issue 11 (November 2014) - Miloslavsky, E. M.; Specks, U.; Merkel, P. A.; Seo, P.; Spiera, R.; Langford, C. A.; Hoffman, G. S.; Kallenberg, C. G. M.; St.Clair, E. W.; Tchao, N. K.; Viviano, L.; Ding, L.; et al.
<x xml:space="preserve">Abstract</x> Objective Disease relapses are frequent in antineutrophil cytoplasmic antibody–associated vasculitis (AAV). This study was undertaken to evaluate outcomes in patients with AAV who are re‐treated with rituximab (RTX) and prednisone for severe disease relapses. Methods The Rituximab in AAV trial was a randomized, double‐blind, placebo‐controlled trial comparing the rates of remission induction among patients treated with RTX (n = 99) and patients treated with cyclophosphamide (CYC) followed by azathioprine (AZA) (n = 98). Prednisone was tapered to discontinuation after 5.5 months. After remission was achieved, patients who experienced a severe disease relapse between months 6 and 18 were eligible to receive RTX and prednisone on an open‐label basis according to a prespecified protocol. Investigators remained blinded with regard to the original treatment assignment. Results Twenty‐six patients received RTX for disease relapse after remission had initially been achieved with their originally assigned treatment. Fifteen of these patients were initially randomized to receive RTX and 11 to receive CYC/AZA. Thirteen (87%) of the patients originally assigned to receive RTX and 10 (91%) originally assigned to receive CYC/AZA achieved remission again with open‐label RTX (an overall percentage of 88%). In half of the patients treated with open‐label RTX, prednisone could be discontinued entirely. Patients in this cohort experienced fewer adverse events compared to the overall study population (4.7 adverse events per patient‐year versus 11.8 adverse events per patient‐year). Conclusion Re‐treatment of AAV relapses with RTX and glucocorticoids appears to be a safe and effective strategy, regardless of previous treatment.